MOLECULAR DOCKING STUDY OF NATURALLY OCCURRING COMPOUNDS AS INHIBITORS OF COVID -19 - SREEDEVI A; RETNA A, MALAR; ROBIN KUMAR SAMUEL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The worldwide spread of COVID-19 is an emergent issue to be tackled. Currently, several works in various field have been made in rather short period. The present study aimed to assess bioactive compounds found in medicinal plants as potential COVID-19 Mpro inhibitors using molecular docking study. Methods: The docking analyses were performed by using Autodock, Discovery Studio Visualiser and Igemdock. Results: The binding energy obtained from the docking of 6LU7 with native ligand cupressuflavone is -8.9 kcal/mol. Conclusion: These findings will provide the opportunities to identify the right drug to combat COVID-19.